Problem Fraksionasi Isotop 15 N/14 N dan Mekanisme Pelepasan Non-Thermik di Atmosfer Titan - T Hidayat (Indonesian Journal of Physics, 2003)
Observations of HC15N in the atmosphere of Titan at millimeter and submillimeter wavelengths, combined with the previous observations of HC14N have yielded the isotopic ratio of 15N/14N. This result, unexpectedly, shows that Titan is signicantly enriched in 15N by a factor of 4.2 (Marten et al. 1)), compared to terrestrial value. The data are a key element to trace the formation and evolution of Titan's atmosphere as well as its relation to the global history of the Solar System. To interpret this isotopic anomaly, various plausible mechanisms, leading to isotopic fractionation, are explored. Upper limit of initial nitrogen abundance on Titan is retrieved.